A three-dimensional analysis of finger and bow string movements during the release in archery - Horsak, B.; Heller, M. (Journal of Applied Biomechanics, 2011)
The aim of this paper was to examine finger and bow string movements during archery by investigating a top Austrian athlete (FITA score = 1233) under laboratory conditions. Maximum lateral bow string deflection and angular displacements for index, third, and ring fingers between the full draw position and the end of the release were quantified using a motion tracking system. Stepwise multiple regression analyses were used to determine whether bow string deflection and finger movements are predictive for scoring. Joint ranges of motion during the shot itself were large in the proximal and distal interphalangeal joints, and much smaller in the metacarpophalangeal joints. Contrary to our expectations, greater deflection leads to higher scores (R2 = .18, p < .001) and the distal interphalangeal joint of the third finger weakly predicts the deflection (R2 = .11, p < .014). More variability in the joint angles of the third finger was found in bad shots than in good shots. Findings in this study let presume that maximum lateral bow string deflection does not adversely affect the archer`s performance.